Global forces and national Institutions: call centre work in Colombia. (1st July 2007) - ,
Abstract : The aim of this article is to contribute to the discussion about the relationship between global forces and national institutions, from a Latin American perspective. In addition to presenting some data about the diffusion of information and communications technologies in Latin America, we try to establish the relationship between some characteristics of Colombian society and the particular nature of the working conditions and employment relationships in call centres in this country, drawing on some exploratory case studies of call centres carried out in 2004, that formed part of a larger ongoing research project. It concludes that several features that are specific to the Colombian context appear to play a major role in shaping working conditions in Colombian call centres, including the particular characteristics of the labour market, the low regulatory power of the State, low compliance with labour laws, the persistence of the armed conflict that weakens all social and labour movements and the existence of a ''culture of distrust''. This suggests that the national institutional environment exerts an important role in shaping local working conditions, even when powerful global forces are at play.